Cueing dancers to "externally rotate from the hips" improves potentially injurious ankle joint angles and contact forces during a demipointe ballet position - Hulburt, T.; Santos, L.; Moos, K.; Popoli, D.; Nicholson, K. (Journal of Dance Medicine & Science, 2024)
Introduction The demipointe dance position puts the ankle at high risk of overuse injury and posteromedial ankle pain due to increased ankle valgus forces. Previous work has shown that creating lower limb external rotation intrinsic to demipointe with hip external rotation reduces foot pronation that causes ankle valgus stress. Therefore, the purpose of this work was to examine long axis rotation kinematics of the hip, knee, and ankle as well as the ankle joint contact forces in demipointe to better understand the biomechanical impact(s) of the specific cue to increase hip external rotation in this position.